Using a computer game to teach circuit concepts. (19th August 2019) - Kortemeyer, Gerd; Anderson, Daniel; Desrochers, Ann Marie; Hackbardt, Amanda; Hoekstra, Kelsie; Holt, Alexander; Iftekhar, Asif; Kabaker, Tyler; Keller, Nicole; Korzecke, Zosha; Gogonis, Angelos; Manson, Quincy; et al.
Abstract: We describe the development and use of Kirchhoff ' s Revenge, a freely available computer game designed to teach circuit laws in introductory physics courses at the high-school and undergraduate level. In this case study, we describe design principles, effort involved in developing the game, as well as player experiences and feedback. We also report on concept-test results for time-independent scenarios (batteries, wires, and lightbulbs), where we find that conceptual learning gains from playing the game alone are similar to those from traditional instruction alone, but inferior to a combination of traditional instruction with investigative, physical laboratory experiments.